Millennial Women's Understanding in Aceh on Islamic Education, Jihad, and Suicide Bombing in Sibolga - Raihan, Raihan; Muhammad Ichsan; Muzakir; Nurma Dewi; Fakhrul Rijal; Putri Ananda Sari (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The discussion on jihad and suicide bombings in Indonesia shows a new pattern of jihadists and suicide bombers recruiting young women. Jihad is defined by the ulama as a genuine human effort to worship Allah SWT, but there are some people who misinterpret this meaning. This research is field research using a qualitative approach. This research was conducted at three universities in Aceh, namely Teuku Umar University (UTU) in Meulaboh, Malikus Saleh University Lhokseumawe, and IAIN Gajah Puteh in Takengon. Because this research highlights the knowledge of jihad in young women, the research object is female students at the three universities. Meanwhile, data collection techniques include interviews, documentation and social media observations regarding the phenomenon of knowledge of jihad and suicide bombings. The results of this research show that millennial women are less familiar with the word jihad, however, millennial women have their own reasoning about jihad. In response to the Sibolga bomb, the news was not followed closely, but millennial women did not agree with the teachings of the Islamic religion being conveyed in a violent manner.